Effect of long-term moisture exposure on impact response of glass-reinforced vinylester. (November 2021) - Alizadeh, Fatemeh; Kharghani, Navid; Guedes Soares, Carlos
Glass/Vinylester composite laminates are comprehensively characterised to assess its impact response behaviour under moisture exposure in marine structures. An instrumented drop weight impact machine is utilised to determine the impact responses of dry and immersed specimens in normal, salted and sea water. The specimens, which had three different thicknesses, were subjected to water exposure for a very long period of over 20 months before tested in a low-velocity impact experiment. Water uptake was measured primarily to study the degradation profiles of GRP laminates after being permeated by water. Matrix dissolution and interfacial damage observed on the laminates after prolonged moisture exposure while the absorption behaviour was found typically non-Fickian. The weight of the composite plates firstly increased because of water diffusion up to month 15 and then decreased due to matrix degradation. The specimens with 3, 6 and 9 mm thickness exhibited maximum water absorption corresponding to 2.6%, 0.7% and 0.5% weight gain, respectively. In general, the results indicated that water uptake and impact properties were affected by thickness and less by water type. Impact properties of prolonged immersed specimens reduced remarkably, and intense failure modes detected almost in all cases. The least sensitive to impact damage were wet specimens with 9 mm thickness as they indicated similar maximum load and absorbed energy for different impact energies.